Produktiwiteitsverhoging: ’n bestuurswetenskaplike en prinsipiële beskouing - Kruger, S. (Koers, 1991)
The pursuit of high productivity is not a goal in itself, but rather regulates the attempt to raise a country's standard of living. Since the standard of living is dependent on the relationship between the total output and input of all businesses, the productivity of a single business has a great influence. Increasing productivity is considered to be an extremely important management function. I f productivity is regarded as the measuring instrument of successful management, then the management process and, more specifically, management by objectives is the method for achieving this. It is management’s responsibility to create the necessary climate of productivity and increased productivity. The approach must be one which achieves a balance between task-orientation and people-orientation. Consequently the purpose and meaning of work should also be reconsidered. Work is not a goal in itself but must always be seen within the wider context of God’s cultural mandate to man. When everyone understands the meaning of work we will emerge from the so-called ‘reward psychosis’, and reward will be offered according to need and achievement. Reward and work fulfilment will lead to the creation of a work environment which is meaningful of the worker, which promotes increased productivity, and which allows self-actualization toflourish. Management is capable of creating and maintaining these circumstances which will increase productivity.